PENGEMBANGAN KAPASITAS BAWASLU KOTA DALAM PELAKSANAAN PENGAWASAN PEMILIHAN GUBERNUR TAHUN 2020 DI KOTA PALANGKA RAYA - Tangkasiang, Bramulia (JURNAL SOCIOPOLITICO, 2023)
Capacity building is a strategy aimed at increasing efficiency, effectiveness and responsiveness that focuses on the dimensions of human resource development and organizational strengthening. The purpose of this study was to identify and describe capacity building and the factors that influence the capacity development of the Municipal Election Supervisory Board in supervising the 2020 gubernatorial election in the City of Palangka Raya. The data collection techniques used interviews and documentation studies, while the data analysis techniques used qualitative data analysis which included data reduction, data presentation and drawing conclusions.The results showed that the capacity development of the Election Supervisory Board for the City of Palangkaraya from the human resource dimension was carried out through technical guidance, training, seminars, technical coordination meetings and internal meetings, while from the dimension of organizational strengthening, namely institutional recruitment of the Election Supervisory Board for the City of Palangkaraya was permanent. strengthening the duties, obligations and authorities of the Election Supervisory Board for the City of Palangkaraya, emphasizing the prevention aspect in the implementation of the supervisory function and the existence of law enforcement authority through the Integrated Law Enforcement Center. The factors that influence the capacity building of the Election Supervisory Board for the City of Palangkaraya are (a) a joint commitment in the form of a conducive, harmonious, mutually respectful relationship between members and staff of the Election Supervisory Board for the City of Palankaraya and the existence of a joint commitment between the election supervisory body for the City of Palangkaraya, the Attorney General's Office and the Police in the Integrated Law Enforcement Center, (b) conducive and dynamic leadership and the ability of the Chairperson of the Election Supervisory Board for the City of Palangkaraya managerially and technically, (c) regulatory reform by changing the rules of the Election law from law number 15 of 2011 became law number 7 of 2017 had a positive impact on the authority of the election supervisory board for the City of Palangkaraya and became a permanent institution, and (d) structural institutional reform of the election/pilkada supervisory agency and the work culture of members and staff of the City Election Supervisory Board Palangkaraya.